Mechanical and durability properties of sand cement brick containing recycled concrete aggregate and crumb rubber as partial sand replacement material - Aminuddin, Mohamad Yuzwan Aliff (2021)
During the last decades, it has been recognized with growing concern that wastes from a construction and demolition (C&D) are large volume and that this is increasing year by year. The problem of waste accumulation exists worldwide. Most of waste materials are left as a landfill material or illegally dumped. Environmental impact can be reduced by making more sustainable use of this waste by recycling process. This study aims to establish the sustainable properties for sand cement bricks using Recycle Concrete Aggregate (RCA) and Crumb Rubber (CR) as partial sand aggregate replacement materials. The objectives of this study are to measure the optimum cement-sand ratio (1:5, 1:6 and 1:7) for sand cement brick through density, compressive strength and water absorption tests. The mechanical properties and durability of sand cement bricks through shrinkage and carbonation as well as the optimum percentages of RCA and CR as sand aggregate replacement in sand cement bricks was also investigated. The brick specimens were prepared using 15%, 30%, 45% and 60% of RCA and 1.5%, 3.0%, 4.5% and 6.0% of CR by volume of sand with a water-cement ratio of 0.6. The size of the RCA used was less than 5 mm. Moreover, the size of the sieved waste CR granules is between 0.1 to 5 mm which made it physically similar to the size of fine aggregates. The overall results revealed that the best cement-sand ratio was 1:6. The density test indicates that the average density of sand cement bricks is lower compared to that of control bricks. In addition, the percentage of water absorption for sand cement bricks was found to be satisfactory. In a nutshell the optimal replacement of RCA and CR was R15C1.5 with a cement-sand ratio of 1:6 as it achieved the lowest values during the drying shrinkage and carbonation tests.